Continuing professional development needs in pain management for Canadian health care professionals: A cross sectional survey. Issue 1 (31st December 2023) - Dale, Craig M.; Cioffi, Iacopo; Novak, Christine B.; Gorospe, Franklin; Murphy, Laura; Chugh, Deepika; Watt-Watson, Judy; Stevens, Bonnie
ABSTRACT: Background: Continuing professional development is an important means of improving access to effective patient care. Although pain content has increased significantly in prelicensure programs, little is known about how postlicensure health professionals advance or maintain competence in pain management. Aims: The aim of this study was to investigate Canadian health professionals' continuing professional development needs, activities, and preferred modalities for pain management. Methods: This study employed a cross-sectional self-report web survey. Results: The survey response rate was 57% (230/400). Respondents were primarily nurses (48%), university educated (95%), employed in academic hospital settings (62%), and had ≥11 years postlicensure experience (70%). Most patients (>50%) cared for in an average week presented with pain. Compared to those working in nonacademic settings, clinicians in academic settings reported significantly higher acute pain assessment competence (mean 7.8/10 versus 6.9/10; P < 0.002) and greater access to pain specialist consultants (73% versus 29%; P < 0.0001). Chronic pain assessment competence was not different between groups. Top learning needs included neuropathic pain, musculoskeletal pain, and chronic pain. Recently completed and preferred learning modalities respectively were informal and work-based: reading journal articles (56%, 54%), online independent learning (44%, 53%), and attending hospital rounds (43%, 42%); 17% had not completed any pain learning activities in the past 12 months. Respondents employed in nonacademic settings and nonphysicians were more likely to use pocket cards, mobile apps, and e-mail summaries to improve pain management. Conclusions: Canadian postlicensure health professionals require greater access to and participation in interactive and multimodal methods of continuing professional development to facilitate competency in evidence-based pain management.